Factors Related to Premature Rupture of Membranes (PROM) - Shinta Novelia; Tommy J Wowor; Indriyani (KHD Production, 2023)
One of the contributors to morbidity and mortality rates in mothers and babies is infection caused by premature rupture of membranes (PROM), where the amniotic membrane which is a barrier to the entry of germs that cause infection is no longer there and can be dangerous for the mother and fetus. This study aims to determine the factors associated with the incidence of premature rupture of membranes at the Ciruas Health Center in 2018. The study design is cross sectional. The population is 140 childbearing women who were in the Ciruas Health Centre during study period. 33 women were selected purposively as the sample based on inclusion and exclusion criteria. The results show that the incidence of PROM at the Ciruas Community Health Center was quite high (63.6%). Most of the mothers who gave birth had a high risk of giving birth (60.6%), were primiparous (51.5%), had a term gestational age (63.6%), and lacked knowledge about pregnancy and childbirth (54.5%). There was a relationship between age (p=0.003), parity (p=0.008), gestational age (p=0.010), and knowledge (p=0.027) with the incidence of premature rupture of membranes in in childbirth women at the Ciruas Health Center in 2018. It is hoped that the community health center can provide intensive delivery services to mothers who are at high risk of experiencing PROM. Apart from that, it is also necessary to provide counseling, information, and education regarding danger signs during labor for mothers who are giving birth.